Teaching Graphic Design for undergraduate students in Vietnam: a curriculum analysis - Quyen, Tran Thi Le; Liou, Shyhnan; Yang, Chia Han (Frontiers in Education, 2024)
The present study aims to examine the effects of autonomy policies implemented after 2014 on the undergraduate education of Graphic Design in Vietnam. This study employs a targeted analysis of specialized knowledge courses, specifically tracing their progression from conventional design principles for print medium to modern digital design principles. A comprehensive examination of curricular adjustments is conducted, providing a clear understanding of the changes in educational priorities. Prior to 2014, the Curriculum mostly focused on traditional design concepts that were specifically designed for print media. These elements included typography, layout, and color theory. Nevertheless, a notable shift took place subsequent to 2014, resulting in a Curriculum that better corresponds to the requirements of the digital era. This transition signifies a significant change towards digital design for online platforms, encompassing essential aspects such as responsive design, user experience/user interface, motion graphics, and animation. The study's presentation of empirical data highlights the significant influence that enhanced institutional autonomy has on the transformation of Graphic Design education. The transition from traditional print media to digital platforms has been a significant development, coinciding with a growing acceptance and adoption of interdisciplinary methodologies. The aforementioned modifications are a direct reaction to the dynamic requirements of contemporary design practice, which is distinguished by the extensive impact of digital technology, interactivity, and increased considerations regarding sustainability. The results emphasize the significance of integrating Graphic Design education with the changing demands of the modern industry. The aforementioned realignment guarantees that graduates possess the necessary skills and knowledge to thrive in the digital age.